Remittances to Developing Countries Will Surpass $400 Billion in 2012 - Ratha, Dilip; Aga, Gemechu Ayana; Silwal, Ani (World Bank, Washington, DC, 2014)
The officially recorded remittances to developing countries are expected to reach 406 billion dollar in 2012, up by 6.5 percentage from 381 billion dollar in 2011. The true size of remittance flows, including unrecorded flows through formal and informal channels, is believed to be significantly larger. Compared to private capital flows, remittance flows have shown remarkable resilience since the global financial crisis, registering only a modest fall in 2009, followed by a rapid recovery. The size of remittance flows to developing countries is now more than three times that of official development assistance.